Sistem Informasi Layanan Kependudukan Desa Karang Sari Muara Enim Berbasis Web Menggunakan Php Dan Mysql - Heru Saputra; Dian Sri Agustina (Jurnal Informatika dan Komputer (JIK), 2021)
Population service information system is a web-based system used to manage the administrative service process of making correspondence. The types of administrative services include domicile certificates, business certificates, temporary id certificates, unmarried certificates, death certificates, certificates of inadequacy. The creation of correspondence in Karang Sari Village still uses bookkeeping atatu archives manually. From the bookkeeping or archive will then be glued into Microsoft Word to be printed as a report, not to mention the officer will serve the community in the creation of correspondence so that in the process it takes more time to perform the service of population administration properly. On the basis of these problems was built a web-based Population Service information system to perform rapid and appropriate administrative services This web-based Information System of Development Services using Php and mysql programming languages serves to facilitate the administrative officer in the Karang Sari Village Head's Office in terms of making correspondence administration. This system has several menus created, namely Home, Mail Data, reports, users, and logout. This Population Service data menu has sub menus namely sub menu of domicile certificates, business certificate sub menus, sub menus of temporary id certificates, sub menus of unmarried certificates, sub menus of death certificates, sub menus of certificates of inadequacy. This research resulted in a website-based mail filing system that contains incoming mail data and outgoing mail data